Comics and Agency - Thon, Jan-Noël; Ossa, Vanessa; Wilde, Lukas R. A. (Comics Studies, 2022)
This volume focuses on the attribution of agency across comics production (authorship and institutionalization), reception (appropriation and discursivation), and circulation (participation and canonization). Contributors from a range of different fields investigate the interrelations between individual, collective, and institutional actors within historical and contemporary comics cultures.